Evaluation of Mechanical Performance of Homopolymer Polypropylene/Kenaf Fibre/ Binder using Full Factorial Method - Md Ali, Mohd Amran; Hilmi, Hazwani; Mohd Sani, Siti Salmah; Abdullah, Zulkeflee; Mohamad, Effendi; Liew , Pay Jun (Penerbit Akademia Baru, 2014)
The mechanical performance of kenaf fibre/homopolymer polypropylene/binder composites was studied. Tensile test was used to investigate the tensile strength, tensile modulus and percentage of elongation. Kenaf fibre-homopolymer polypropylene (KFHPP) composites were compounded in an internal batch mixer with the ratio of 10:90, 30:70 and 50:50 in weight fraction. Furthermore, maleated polypropylene (MAPP) as a binder with 1, 3 and 5 % expressed as percentage of weight ratio was mixed in KFHPP composites. A hot pressing machine was used for producing samples of dog bone. From this study, it is found that the tensile strength and tensile modulus increase with increasing kenaf fibre loading and higher percentage of MAPP. In addition, the elongation at break for KFHPP composites shows lower result for increasing kenaf fibre loading. However, when the percentage of MAPP added to KFHPP composites increases, the elongation at break increased slightly. Thus, the result shows that the binder can enhance the interaction between kenaf fibre and homopolymer polypropylene composites, with resulted in better tensile strength and tensile modulus but less function at elongation at break.